2007
DOI: 10.1258/026835507782655263
|View full text |Cite
|
Sign up to set email alerts
|

Vascular bone syndrome – angio-osteodystrophy: current concepts

Abstract: Congenital vascular bone syndrome (CVBS) is an abnormal enhancement or reduction of growth in long bones due to pathologic circulation during childhood. Several authors have described these clinical pictures with limb lengthening; well known are Klippel and Trenaunay and Parkes-Weber. Later, Servelle and Martorell also described cases of limb length difference, but with shortening of the pathologic limb. The mechanism of limb overgrowth is probably due to the effect of A-V shunts, while shortening occurs due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 10 publications
0
10
0
5
Order By: Relevance
“…7 Bone involvement is so frequent in patients with extensive vascular malformations that some authors include it under the term congenital vascular bone syndrome (CVBS; ie, a pathologic enhancement or reduction in long bone growth related to congenital abnormal circulation). 8 temperature, and augmented oxygenation in the bone caused by arteriovenous fistulae may stimulate the osteoblasts to produce bone overgrowth. 9 However, some authors concluded that the cause of CVBS is venostasis rather than hyperemia after obtaining elongation of long bones in animals by ligation of deep veins, 10 while bone hypotrophy has been related to a mechanical compression on bones by dilated vascular malformations.…”
Section: Learning Objectivesmentioning
confidence: 99%
“…7 Bone involvement is so frequent in patients with extensive vascular malformations that some authors include it under the term congenital vascular bone syndrome (CVBS; ie, a pathologic enhancement or reduction in long bone growth related to congenital abnormal circulation). 8 temperature, and augmented oxygenation in the bone caused by arteriovenous fistulae may stimulate the osteoblasts to produce bone overgrowth. 9 However, some authors concluded that the cause of CVBS is venostasis rather than hyperemia after obtaining elongation of long bones in animals by ligation of deep veins, 10 while bone hypotrophy has been related to a mechanical compression on bones by dilated vascular malformations.…”
Section: Learning Objectivesmentioning
confidence: 99%
“…Each of the original authors presented cases with inexact characteristics and often anecdotal exceptions. Klippel and Trenaunay acknowledged "incomplete" cases without one of the three signs [6]. Subsequent researcher have "published cases of Klippel-Trenaunay syndrome with a-v fistulas, cases of Parkes Weber syndrome without fistulas,… [and] cases of Klippel-Trenaunay syndrome with shortening of the limb" [7].…”
Section: Discussionmentioning
confidence: 99%
“…Окрім оцінки пер-винного вогнища АВМ, необхідно обстежити органи і системи, які можуть вторинно уражатися, зокрема опорно-руховий апарат. Рання діагностика судинно-кісткового синдрому, який супроводжується різницею в довжині довгих кісток, є необхідною умовою своєчас-ного й патогенетично обґрунтованого лікування [20]. Базові неінвазивні та мінімально інвазивні ме-тодики, які слід виконати в першу чергу при підозрі на АВМ, включають: УЗД у режимі КДС і Доппле-ра; дуплексну ультрасонографію (артеріальна і ве-нозна); МРТ; КТ-ангіографію з контрастуванням, 3D-реконструкцією.…”
Section: а бunclassified